Open Labware Workshops - Chagas, Andre (My University, 2021)
Slides in .pdf given for the BCGE Workshop: Research Collaboration with Partners in the "Global South". The presentation shows experiences and things learned on the process of organizing and teaching workshops about Open Labware, as part of the efforts from Trend in Africa.
Keywords: Open source; Open Source Hardware; Open Science